Pengaruh Struktur Corporate Governance Dan Risiko Perusahaan Terhadap Fee Audit - Rudy Suryanto; Sinta Aria Dewi Siskawati; Hafiez Sofyani (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2018)
This study aims to analyze and provide empirical evidence of the influence of corporate governance structure and client risk towards audit fees. Corporate governance structure in this study uses the existence of independent commissioner, audit committee and majority shareholder. The bond ratings is used to measure client risk. This study uses secondary data from Indonesian Capital Market Directory (ICMD), annual reports, and bond ratings from PT. PEFINDO of companies which listed on Bursa Efek Indonesia in 2012-2013. This study uses purposive sampling method and resulted 104 firms. The method of analysis of this study used multi regression with SPSS 15.0. Program. The results indicate that corporate governance structure had no influence on audit fees, client risk have a positive influence on audit fees.